2021
DOI: 10.3389/fcell.2021.659080
|View full text |Cite
|
Sign up to set email alerts
|

ANXA1 as a Prognostic and Immune Microenvironmental Marker for Gliomas Based on Transcriptomic Analysis and Experimental Validation

Abstract: The tumor microenvironment (TME) plays an important role in the growth and invasion of glioma. This study aimed to analyze the composition of the immune microenvironment in glioma samples and analyze the important differentially expressed genes to identify novel immune-targeted therapy for glioma. We downloaded transcriptomic data of 669 glioma samples from The Cancer Genome Atlas database. CIBERSORT and ESTIMATE methods were used to calculate the proportion of tumor-infiltrating immune cells and ratio of immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
(48 reference statements)
2
11
0
Order By: Relevance
“…To explore the exhaustive function of ANXA1 in gliomas, we integrated the bulk genomic and transcriptomic profiles and scRNA-seq data to comprehensively characterize the role of ANXA1 in gliomas. In this study, we revealed that ANXA1 was significantly upregulated in GBM patients, especially enriched in IDH wild-type gliomas, which was consistent with previous reports ( Lin et al, 2021 ; Qiu et al, 2020 ). In addition, gliomas with chemotherapy and/or radiotherapy tend to have a high ANXA1 expression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To explore the exhaustive function of ANXA1 in gliomas, we integrated the bulk genomic and transcriptomic profiles and scRNA-seq data to comprehensively characterize the role of ANXA1 in gliomas. In this study, we revealed that ANXA1 was significantly upregulated in GBM patients, especially enriched in IDH wild-type gliomas, which was consistent with previous reports ( Lin et al, 2021 ; Qiu et al, 2020 ). In addition, gliomas with chemotherapy and/or radiotherapy tend to have a high ANXA1 expression.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies suggest that loss of function or expression of this gene has been implicated in multiple functions essential in cancer, including cell proliferation, apoptosis, chemosensitivity, metastasis, and invasion ( Bai et al, 2020 ; Feng et al, 2020 ; Xiong et al, 2021 ). Recently, Lin et al investigated the prognostic and immune role of ANXA1 in gliomas ( Lin et al, 2021 ). However, the systematic and comprehensive transcriptome characterization of ANXA1 in gliomas is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies proven that targeting ANXA1 abrogated Treg-mediated immune suppression in triple-negative breast cancer and ANXA1 was considered as a worse prognostic and TME marker in gliomas. (24, 25) FASN is abnormally expressed in lots of tumors and is highly related to tumor migration and invasion (26). FNDC4 promotes the tumor invasiveness of hepatocellular cancer as an extracellular factor to (27).…”
Section: Discussionmentioning
confidence: 99%
“…Also, our results corroborated these analyses. ANXA1 had just been reported as a prognostic and immune microenvironmental marker in glioma ( Lin et al, 2021 ; Qian et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the IDH1 mutant had been widely recognized as one of the indicators for molecular typing of glioma ( Pirozzi and Yan, 2021 ). Also, ANAX1 , another NRG, might act as a regulator of cell-mediated immunity in low-grade glioma (LGG) TME by activating T cells ( Lin et al, 2021 ). Celastrol derivatives were verified as novel potential selections in glioma therapy due to their functions in necroptosis ( Feng et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%